Evaluasi Mikrovaskuler dengan Near Infrared Spectroscopy pada Pasien Kaki Diabetes - Kartika, Ronald Winardi; Timotius, Kris Herawan (Universitas Kristen Krida Wacana, 2024)
Peripheral Arterial Disease (PAP) requires good evaluation to reduce amputation rate. The aim of this study is to assess non-invasive detection methods in evaluating microvascular conditions in PAP. The potential use of Near Infrared Spectroscopy (NIRS) in identifying disorders in patients with PAP, either with or without DM, was also assessed. A systematic literature search was conducted through PUBMED until October 2023. Based on the literature review, it can be concluded that the use of NIRS in evaluating microvascular status in PAP is a non-invasive testing method that has expanded its role. Evaluation with NIRS provides metrics such as recovery time, deoxygenation, oxygen consumption (VO2), tissue oxygen saturation (StO2), total haemoglobin (HbT), and oxyhemoglobin area under the curve (O2 HbAUC). NIRS also has the potential to assist multidisciplinary teams in treating high-risk patients, especially in diabetic patients whose symptoms are compensated by peripheral neuropathy. This study shows that NIRS can be used as a useful tool in evaluating microvascular status in PAP, by providing important information that can be used to optimise patient care and prevent more serious complications. It is concluded that NIRS can be used as a tool to evaluate the effectiveness of treatment and prevent worsening of the condition of patients with PAP in diabetic foot.